Tinjauan Hukum Perlindungan Konsumen dan Tantangan di Dunia Pasar Digital - Thessa Tentua (Jurnal Hukum Lex Generalis, 2026)
The rapid development of digital technology has significantly changed the digital market situation. Consumers now transact more frequently through digital platforms, which provide convenience and efficiency. However, despite some benefits, new challenges arise in terms of consumer protection, especially regarding data security, information transparency and service provider responsibility. This research covers the legal perspectives and legal aspects of consumer protection in the digital market era as well as the barriers faced by consumers and analyzes the applicable regulations in Indonesia and compares them with international practices to provide an understanding of regulations with rapid technological developments, such as e-commerce, fintech and other digital platforms.